Implementation of a Child-Friendly Literature Program in RA Rumah Kreatif Wadas Kelir - Hikmaturrahmah Hikmaturrahmah; Muh. Iksan Akbar; Amalia Nurbaiti (Early Childhood Education & Parenting, 2024)
This study aimed to identify, explain, and analyze the implementation of a child-friendly literacy program at RA Rumah Kreatif Wadas Kelir. This research used a qualitative descriptive research method with the type of field research. This research data collection used observation, interview, and documentation techniques. The results showed that the implementation of the child-friendly literacy program at RA Rumah Kreatif Wadas Kelir was conducted through; first, the activity of borrowing books at the library. This activity is a habit that is carried out every day, and this activity becomes a child-friendly literacy activity. It is indicated by the fact that children are happy to visit the library to borrow interesting books, become fond of books, and have an interest in reading books. In addition, aspects of children's development in the activity of borrowing books are also developed. They include aspects of motoric, social, emotional, and language development. Second, read-aloud activity. It is conducted routinely by the teacher. This is a child-friendly literacy activity. It is marked by children having an interest in reading books, loving to be read to, and when people read a book to them, they are very enthusiastic about listening to the story. Furthermore, aspects of children’s development in reading-aloud activities are also developed. They include aspects of language development, cognitive, and social-emotional. Therefore, borrowing books at the library and reading aloud became fun activities for children.